O sentido do trabalho a partir da experiência de migrantes venezuelanos e seus reflexos na socialização e diversidade no mercado de trabalho - Züge, Aline Aparecida (2021)
Here are multiple motivations that lead an individual to migrate, such as wars, political crimes, escape from poverty and/or calamity, terrorism, among others. More and more individuals are migrating in search of better opportunities, especially employment and better conditions and better quality of life. This study sought to understand the meaning of work, socialization and diversity in the insertion of Venezuelan migrants in the labor market in the municipality of Santa Maria/RS. For this, a descriptive, exploratory qualitative research was carried out. A broad gratitude for the opportunity to be inserted in the labor market was identified; in the perception of effort and valuing of a sympathetic and able group to help with doubts; in the broad sense of learning and in a work environment in which they feel open to expand their knowledge, with a good organizational climate. In the context of work and its meanings, the importance for migrants of keeping busy, having some autonomy in their work activity, performing work that is useful to society, morally accepted and producing satisfactory interpersonal relationships was evident. Those who were dissatisfied with their current work are in this condition, due to devaluation by superiors, the occupation itself and the language barrier. In relation to socialization, it was possible to identify a good integration and adaptation to the organization/company, through its norms, values and customs, to the group/team and the tasks performed, with language being a hindering factor. The majority sought to adapt to the new reality in Brazil, through networking with their colleagues and superiors. In the aspect of insertion in the work environment and their perception and sense of belonging to the group/team, a positive scenario was perceived, although it did not occur unanimously among the participants, highlighting the reports of female interviewees, in who pointed out to feel discriminated against and devalued, as was evident in several moments of the discussion. The work brings to light the perception that it is necessary to formulate and implement public policies for the social inclusion of migrants arriving in Brazil, particularly those received for humanitarian reasons such as Venezuelans. For future studies, we highlight some suggestions outlined in order to broaden and deepen knowledge on migration, meaning of work, diversity and inclusion, which may include the analysis of different angles on the subject analyzed here, especially with regard to the way other employees, in this case Brazilian workers and senior management, deal with inclusion and diversity.